Ocimum sanctum: The Journey from Sacred Herb to Functional Food - Kumari, Sneha; Singh, Preet A.; Hazra, Subhajit; Sindhwani, Ritika; Singh, Sukhvinder (Recent Advances in Food Nutrition & Agriculture, 2024)
In recent years, the growing demand for herbal-based formulations, including functional foods, has acquired significant attention. This study highlights historical, botanical, ecological, and phytochemical descriptions and different extraction mechanisms of Ocimum sanctum utilized in its processing. Besides this, it explores the utilization of Ocimum sanctum as a functional food ingredient in various food products such as bakery products (biscuits, bread), dairy products (herbal milk, cheese), and beverages (tea, juice, wine) while focusing on their evaluation parameters, preparation techniques, and pharmacological activities. In terms of other pharmacological properties, Ocimum sanctum-infused functional foods exhibited cognitiveenhancing properties, adaptogenic qualities, anti-obesity effects, gastroprotective, antiinflammatory, hypoglycemic, and immuno-modulatory effects. Thus, the diverse properties of Ocimum sanctum offer exciting opportunities for the development of functional foods that can promote specific health issues, so future research should focus on developing and analyzing novel Ocimum sanctum-based functional foods to meet the growing demand of the functional food industry.
Keywords: tulsi